A comparison of removal efficiencies of conventional drinking water treatment and advanced treatment equipped with ozone-biological activated carbon process. Issue 26 (23rd November 2021) - Shen, Hong; Fan, Hongliang; Wu, Nanxiang; Hu, Jun
ABSTRACT : Using raw water from a shallow water supply reservoir located in the lower Yangtze River region, the removal efficiencies of conventional treatment on dissolved organic matter (DOM) and disinfection by-products formation potential (DBPFP) were compared with an advanced treatment that equipped with ozone-biological activated carbon (O3 -BAC) process. The results showed that the advanced treatment was more efficient than the conventional treatment at removing dissolved organic carbon (DOC; 40–67% removal), UV254 (61–81% removal), the trihalomethane formation potential (THMFP; 37–70% removal) and the haloacetic acid formation potential (HAAFP; 35–89% removal). The sand filter in the conventional treatment process was identified as the main contributor to decreasing DOC, UV254 and DBPFP. The O3 -BAC in advanced treatment was found to decrease THMFP and HAAFP, with removal rates of 17–40% and 22–59%, respectively. To improve the water quality of effluents, advanced treatment with O3 -BAC should be used to treat raw water from the shallow water supply reservoir in lower Yangtze River. However, the increased DBPFP yield, which is proportional to the potential health risks, should not be ignored. GRAPHICAL ABSTRACT: UF0001